2019
DOI: 10.5897/ajb2018.16741
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological stability of muffins packed in actives edible coatings from cassava starch: Inverted sugar/sucrose and natural additives

Abstract: The aim of this study was to develop edible coatings containing natural additives incorporated to the matrix of cassava starch, for use in muffins, as well as to evaluate the efficacy of its use in the increase of shelf life and maintenance of the products characteristics. Seventeen film forming formulations were developed following a central composite experimental design (CCD). The influence of independent variables (soluble coffee, cocoa powder and propolis extract) was determined on the sensorial (colour, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Water activity of control increased from 0.76 at zero day to 0.83 at 21st day of storage bread. Similar trend was observed[4,32].…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Water activity of control increased from 0.76 at zero day to 0.83 at 21st day of storage bread. Similar trend was observed[4,32].…”
supporting
confidence: 89%
“…Chewiness is a parameter of texture easily related to the sensorial analysis through trained panels and can be directly proportional to the hardness and cohesiveness, making it different from elasticity. This can be verified in the evaluation of the variables correlations, where it was possible to note the existence of a directly proportional correlation of this variable with hardness (R2 = 0.96) and an inversely proportional correlation with humidity and Wa (R2 = 0.58 and 0.65, respectively) [4].…”
Section: Effect Of Storage On Water Activity (Aw) Of Muffn Productsmentioning
confidence: 62%
See 2 more Smart Citations
“…Less commonly, the spoilage is caused by bacteria, as this is due to reduced water activity in some products and also to a reduced pH [ 23 ]. A number of researchers found that edible coatings with bee wax, oils from various seeds, herbs and spices, nano emulsions, as well as the preservative nisin, demonstrated increased efficacy on the molds’ growth in bread and sweet bakery products [ 24 , 25 , 26 , 27 , 28 ]. Coatings prepared with chitosan are also proven to have fungicidal activity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%